Bifunctional DNA Architectonics: Three‐Way Junctions with Sticky Perylene Bisimide Caps and a Central Metal Lock. Issue 38 (5th August 2014) - Stubinitzky, Claudia; Bijeljanin, Andrea; Antusch, Linda; Ebeling, Daniel; Hölscher, Hendrik; Wagenknecht, Hans‐Achim
Abstract A new type of a bifunctional DNA architecture based on a three way junction is developed that combines the structural motif of sticky perylene bisimide caps with a tris‐bipyridyl metal ion lock in the center part. A clear stabilizing effect was observed in the presence of Fe3+, Ni2+ and Zn2+ by the formation of corresponding bipyridyl complexes in the branching part of the DNA three way junctions. The dimerization of the 5′‐terminally attached perylene diimides (PDI) chromophores by hydrophobic interactions can be followed by significant changes in the UV/Vis absorption and steady‐state fluorescence. The PDI‐mediated DNA assembly occurs at temperatures below the melting temperature and is not influenced by the metal‐ion bipyridyl locks in the central part. The corresponding AFM images revealed the formation of higher‐ordered structures as the result of DNA assemblies mediated by the PDI interactions.